The impact of national tourism day festivals on inbound tourism: A spatial difference-in-differences approach - Jiafeng Gu (Tourism Economics, 2024)
A comprehensive and accurate assessment of the policy effect of national tourism days is of great significance to further promote urban inbound tourism. Based on the panel data of 59 cities in China from 2000 to 2017, this paper evaluates the local and spatial spillover effects of the China Tourism Day policy on urban inbound tourism using a spatial difference-in-differences model based on the establishment of the China Tourism Day as a quasi-natural experiment. The study found that the China Tourism Day policy significantly increased the number of foreign tourists in cities but significantly reduced their average length of stay, with a positive spatial spillover effect on inbound tourism in surrounding cities.